Two cytotoxic squalene-derived polyethers from the Japanese red alga Chondria armata - Toshiyuki Hamada; Kazushi Kobayashi; Naomichi Arima; Fumito Tani; Charles Santhanaraju Vairappan; Satoaki Onitsuka; Hiroaki Okamura (2020)
The red alga Chondria armata is known to produce and contain a rich diversity of secondary metabolites, such as domoic acid-related alkaloids and triterpene polyethers. Our investigation on red alga C. armata from Kagoshima coast, Japan, resulted in the isolation of two new triterpene polyethers, bandokorols A (1) and B (2). The structures of these compounds were determined based on spectroscopic data such as infrared (FTIR), 1H-NMR, APT, 1H–1H-COSY, HSQC, HMBC, NOESY and FAB mass spectrometry (HRFABMS). The anticancer potentials of these compounds were tested against adult T-cell leukaemia (ATL), S1T cells and their IC50 values are reported here.